Implementation of the SAW Method in the Decision Support System for Contract Extension Freelance Daily Workers - Muhammad Alwi Hanif Lubis; Ruri Ashari Dalimunthe; Suparmadi Suparmadi (Building of Informatics, Technology and Science (BITS), 2022)
The Department of Population and Civil Registration of Asahan Regency provides a freelance daily worker contract extension (THL) which is carried out once a year. Previously, the labor contract extension process was carried out by the head of the personnel sub-section directly in the field and then proposed to the Regional Personnel Agency (BKD) for approval. Then the BKD Office of Asahan Regency gave a contract extension letter to be distributed to contract extension workers who deserved to be extended the contract through the head of the civil service sub-section of the Asahan Regency Population and Civil Registry Office. However, with the number of proposals and the many criteria used in the assessment, this makes it difficult for the Dinas to make decisions about who is entitled to apply for an extension of their work contract. The solution to the problem of extending the contract for casual daily workers (THL) at the Department of Population and Civil Registry of Asahan Regency is by making a decision support system for extending the contract for casual daily workers using the SAW method.